2010
DOI: 10.4269/ajtmh.2010.09-0442
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pica with Anemia and Gastrointestinal Distress among Pregnant Women in Zanzibar, Tanzania

Abstract: * Indicates significance of difference by t -tests between no pica and any pica groups. † Values are mean (SD). 147PICA, ANEMIA, AND GI DISTRESS IN ZANZIBAR, TANZANIA The prevalence of IDA followed a similar pattern, with the prevalence of IDA significantly higher among amylophagists than among those who reported no pica at any point in pregnancy (52.6% versus 36.1%; P < 0.001) and highest among women who ate both pica substances (57.0% versus 36.1%; P < 0.001) ( Figure 2 ). The effect of uncooked rice and ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 50 publications
3
108
1
1
Order By: Relevance
“…2 We propose an explanation for this rate in the fact that we included non-pregnant women undergoing gynecologic surgery and excluded occasional kaolin consumers in the study. As a matter of fact, the strong desire for kaolin ingestion by pregnant women is known, and explained mostly by cultural reasons and gastric discomfort relief (7)(8). However, rates reported in South-America are similar to ours.…”
Section: Discussioncontrasting
confidence: 54%
“…2 We propose an explanation for this rate in the fact that we included non-pregnant women undergoing gynecologic surgery and excluded occasional kaolin consumers in the study. As a matter of fact, the strong desire for kaolin ingestion by pregnant women is known, and explained mostly by cultural reasons and gastric discomfort relief (7)(8). However, rates reported in South-America are similar to ours.…”
Section: Discussioncontrasting
confidence: 54%
“…45,46 A recent meta-analysis found that pica was significantly associated with an increased risk for anemia and low hemoglobin, hematocrit, and plasma zinc. 27 However, there are no published studies that we are aware of that have been able to establish a causal relationship between geophagy and micronutrient status.…”
Section: Discussionmentioning
confidence: 99%
“…3 This behavior is practiced by both children and adults and has been found to be associated with micronutrient deficiency, anemia, enteric distress, soil-transmitted helminth infections, and hunger. [3][4][5][6][7][8] Nonetheless, the direction of the causal relationship for many of these associations and whether geophagy serves as a risky or protective behavior is still debated. 6,7 Beyond the learned behaviors of geophagy, soil ingestion is also an involuntary behavior as part of mouthing and exploration in young children.…”
Section: Introductionmentioning
confidence: 99%